Problems in Implementing Electronic Land Registration At the Pekalongan Regency Land Office - Bakti, Agung Setya; Setyawati, Setyawati; Winjaya Laksana, Andri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This research aims toThis study aims to determine and analyze the implementation, obstacles, and solutions for electronic land registration at the Pekalongan Regency Land Office. This study uses a sociological legal approach. Primary data collection involved interviews, literature studies, and documentation studies. Data analysis was conducted using a qualitative descriptive approach. Based on this study, it was concluded that the implementation of electronic land registration at the Pekalongan Regency Land Office iscan provide many benefits to the community, including minimizing fraud, minimizing brokers/land mafia, preventing corruption, preventing double certificates, saving costs, preventing disputes, conflicts and land cases, minimizing physical meetings, and reducing intervention by unauthorized parties. The implementation of electronic land services can be done through the Sentuh Tanahku application. The result of the implementation of electronic land registration is an electronic certificate. Electronic certificates are legally valid for use as evidence and can provide legal certainty because they are guaranteed by statutory regulations, namelyRegulation of the Minister of ATR/BPN No. 3 of 2023and Law Number 19 of 2016 Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. Obstacles and solutions faced in implementing electronic land registration at the Pekalongan Regency Land Officenamely the limited public understanding of electronic certificates, the lack of completeness of land registration application files, the Human Resources (HR) implementers who are still very limited and not ready to implement electronic land registration, the problem of an uneven internet network, and the implementation of land mapping that is not evenly distributed. Solutions that can be implemented to overcome these obstacles are through information dissemination activities or socialization to the community, conducting training or training and workshops for BPN and PPAT employees, collaborating with internet providers in order to equalize the network, accelerating updates and security of the land system and improving the Sentuh Tanahku application and strengthening security so that it is not easily hacked by irresponsible parties. In addition to these obstacles there are still problems in electronic land registration, namely the legal aspects and legal umbrella related to the legal force of certificates caused by technical regulations and concerns about data and cyber security.